Electrochemically deposited interconnected porous Co3O4 nanoflakes as anodes with excellent rate capability for lithium ion batteries. Issue 45 (20th May 2015) - Zheng, Yunxian; Qiao, Li; Tang, Jun; Yang, Zhibo; Yue, Hongwei; He, Deyan
<x xml:space="preserve">Abstract</x> Prepared by a simple electrochemical deposition technique, interconnected porous Co3O4 nanoflakes grown on nickel foam showed excellent electrochemical performance.